Risk factors for patellar tendinopathy: a systematic review of the literature. Issue 5 (2nd March 2011) - van der Worp, Henk; van Ark, Mathijs; Roerink, Saskia; Pepping, Gert-Jan; van den Akker-Scheek, Inge; Zwerver, Johannes
Abstract : Patellar tendinopathy (PT) is an injury with a high prevalence in sports. Knowledge of risk factors is essential for developing preventive measures and rehabilitation programmes. However, risk factors associated with PT have not yet been systematically studied. This review was undertaken to identify risk factors associated with PT. The literature was systematically searched to identify articles that investigated risk factors for PT. There was no strong or moderate evidence that any investigated risk factor was associated with PT. For nine risk factors there was some evidence: weight, body mass index, waist-to-hip ratio, leg-length difference, arch height of the foot, quadriceps flexibility, hamstring flexibility, quadriceps strength and vertical jump performance. Based on the present evidence, reducing body weight, increasing upper-leg flexibility and quadriceps strength and the use of orthotics may be beneficial treatment options. However, it should be stressed that the evidence for the nine identified risk factors was only limited. Therefore, there is a clear need for high-quality studies in order to identify the exact risk factors associated with PT.